A new endemic species of Macropsychanthus (Leguminosae: Papilionoideae) from the Brazilian Atlantic Forest - Fonseca-Cortés, Andrés; Cardoso, Domingos Benício Oliveira Silva; Snak, Cristiane; Queiroz, Luciano Paganucci De (Phytotaxa, 2023)
The Brazilian Atlantic Forest is a world’s remarkable biodiversity hotspot, seriously endangered by urbanization, industrialization, and agricultural expansion. More than a thousand species of legumes (Leguminosae) occur in the Atlantic Forest, with a record of 443 endemic species. Here, we describe Macropsychanthus ruschii, a new species narrowly endemic from a pristine Atlantic Forest area in the Espírito Santo state, eastern Brazil. This species is uniquely characterized by its inflorescences up to 15 cm and uncommon pink petals. A molecular phylogenetic analysis of nuclear ribosomal (ETS and ITS) and plastid (trnK/matK) DNA sequence data strongly resolves the new species within a clade that exclusively diversified in the Atlantic Forest. This result reinforces the importance of focusing more efforts to conserve and promote biodiversity research in this taxonomically and evolutionarily rich Brazilian phytogeographic domain.